Electrode-diaphragm assembly for alkaline water electrolysis. Issue 5 (December 2020) - Kuleshov, V N; Kurochkin, S V; Kuleshov, N V; Blinov, D V; Grigorieva, O Y
Abstract: In connection with the development of hydrogen energy, special attention is currently being paid to the creation of highly efficient water electrolyzers, including electrolyzers with alkaline electrolyte. The main disadvantage of hydrogen production by water electrolysis is its high energy consumption. The present article shows that energy consumption can be reduced by changing of the electrodes and diaphragm layout. The phase inversion method used for the manufacture of polymer-based porous diaphragms for alkaline water electrolysers made it possible to create an electrode-diaphragm assembly, where elements of electrode-diaphragm assembly represent a single element. The comparative research of electrolysis cells with different electrode-diaphragm assemblies and cells of the traditional "zero gap" was carried out.